Femoral Mycotic Aneurysm Secondary to Community: Acquired Methicillin: Resistant Staphylococcus aureus Infection - Fahad Fayyaz Butt; Mohamed Ashraf Kandath; Fatima Farid Mir; Thouqeer Ahmed (Dubai Medical Journal)
We present the case of a thirteen-year-old, morbidly obese boy admitted with right hip septic arthritis and severe sepsis. Blood and joint aspirate cultures confirmed growth of methicillin-resistant Staphylococcus aureus. Parenteral antibiotic therapy was administered according to culture sensitivity reports, and several joint re-explorations were required for drainage of pus recollection at the hip site. Over a month-long inpatient stay culminated in an episode of profuse fresh bleeding from the right hip wound site, with subsequent CT angiography confirming mycotic aneurysm development at the deep branch of the femoral artery. Emergent endovascular embolization and coil insertion ensued, allowing steady improvement till discharge home.